Modelling the Effects of Soil Conditions on Olive Productivity in Mediterranean Hilly Areas - Ashraf Tubeileh; Francis Turkelboom; Anwar Al-Ibrahem; Richard Thomas; Kholoud Sultan-Tubeileh (International Journal of Agronomy)
The majority of olive (Olea europaea L.) production in Mediterranean environments is characterized by low external inputs and is practiced in hilly areas with shallow soils. This study aimed to study the yield and nutritional status for olive (cv. “Zeiti”) trees in northwestern Syria and establish correlations between yield, on the one hand, and soil/land factors and tree nutrition, on the other hand, to determine the most yield-affecting factors. Land and soil fertility parameters (field slope, soil depth, and soil nutrients) and concentrations of leaf minerals were determined. As olive roots can go deep in the soil profile to extract nutrients, the total available nutrients per tree (over the whole profile) were estimated. Multiple regression analyses were performed to determine the model that best accounts for yield variability. Total available soil potassium amount (R2=0.68), soil total N amount (R2=0.59), and soil depth (R2=0.56) had the highest correlations with olive fruit yields. Available soil potassium amount and soil depth explained together 77% of the yield variability observed. In addition to these two factors, adding leaf B and Fe concentrations to the model increased the variability explained to 83%.